Solving the Puzzle: Connecting a Heterologous Agrobacterium tumefaciens T6SS Effector to a Pseudomonas aeruginosa Spike Complex - Wettstadt, Sarah; Lai, Erh-Min; Filloux, Alain (Frontiers in Cellular and Infection Microbiology, 2020)
The type VI secretion system (T6SS) is a contractile injection apparatus that translocates a spike loaded with various effectors directly into eukaryotic and prokaryotic target cells. Such T6SS spike consists of a needle-shaped trimer of VgrG proteins topped by a conical and sharp PAAR protein that facilitates puncturing of the target membrane. T6SS-delivered effector proteins can be either fused to one of the two spike proteins or interact with either in a highly specific manner. In Agrobacterium tumefaciens the T6SS effector Tde1 is targeted to its cognate VgrG1 protein. Here, we attempted to use a VgrG shuttle to deliver a heterologous T6SS effector by directing Tde1 onto a T6SS spike in Pseudomonas aeruginosa. For this, we designed chimeras between VgrG1 from A. tumefaciens and VgrG1a from P. aeruginosa and showed that modification of the spike protein hampered T6SS functionality in the presence of the Tde1 effector complex. We provide evidence suggesting that Tde1 specifically binds to the VgrG spike in the heterologous environment and propose that there are additional requirements to allow proper effector delivery and translocation. Our work sheds light on complex aspects of the molecular mechanisms of T6SS delivery and highlights some limitations on how effectors can be translocated using this nanomachine.